2004
DOI: 10.1111/j.0006-341x.2004.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Prentice's Approach and the Meta‐Analytic Paradigm: A Reflection on the Role of Statistics in the Evaluation of Surrogate Endpoints

Abstract: Summary. We put a perspective on the strengths and limitations of statistical methods for the evaluation of surrogate endpoints. Whereas using several trials overcomes some of the limitations of a single-trial framework (Prentice, 1989, Statistics in Medicine 8, 431-440), arguably the evaluation of surrogate endpoints can never be done using only statistical evidence but such evidence should be seen as but one component in a decision-making process that involves, among others, a number of clinical and biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 14 publications
0
76
0
Order By: Relevance
“…The Prentice criteria are stringent and the evaluation of surrogate endpoints cannot be assessed using only statistical evidence, but should also consider clinical and biological outcomes. 11 One of the greatest advances in cancer research in the last 2 decades has been the demonstration that infection with certain types of HPV is a necessary cause of cervical cancer. 12,13 Using surrogate endpoints in the development of prophylactic vaccines is necessary, as the use of a cervical cancer as endpoint is unethical.…”
Section: Discussionmentioning
confidence: 99%
“…The Prentice criteria are stringent and the evaluation of surrogate endpoints cannot be assessed using only statistical evidence, but should also consider clinical and biological outcomes. 11 One of the greatest advances in cancer research in the last 2 decades has been the demonstration that infection with certain types of HPV is a necessary cause of cervical cancer. 12,13 Using surrogate endpoints in the development of prophylactic vaccines is necessary, as the use of a cervical cancer as endpoint is unethical.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the estimates of the mean structure parameters are affected, which in turn influences the trial-specific treatment effects and the estimation of the trial-level association in MFE approach. It is also important to note that Cortiñas et al (2004) have also observed similar problems, when they fitted a hierarchical model ignoring a level, and the variance associated to the level was of the same magnitude or larger than the variance at the higher level, the association at the higher level was affected. Here a similar pattern can be observed.…”
Section: Mfe Srte Ritementioning
confidence: 85%
“…The adjusted association carries over when data are available on several randomized trials, while the RE can be extended to a trial-level measure of agreement between the effects of treatment of both endpoints. Molenberghs et al (2002) and Alonso et al (2004) pointed out serious issues surrounding the Prentice-Freedman framework. It has been asserted that the criteria set out by Prentice are too stringent (Fleming and DeMets, 1996) and neither necessary nor sufficient for his definition to be fulfilled, except in the special case of binary outcomes (Buyse and Molenberghs, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Alonso and colleagues [28] introduced the likelihood reduction factor (LRF) for general endpoints, to replace R 2 -type measures specific to normal, survival, or discrete endpoints at the patient level. Later, Alonso and Molenberghs [29] proposed an information-theoretic approach to surrogate endpoint evaluation at both individual and trial levels within a meta-analytic setting, designed to accommodate general endpoint types.…”
Section: Discussionmentioning
confidence: 99%